PENGARUH STRATEGI INSIDE-OUTSIDE CIRCLE TERHADAP MINAT BELAJAR IPS SISWA KELAS III SD NEGERI 7 MANURUNGE KECAMATAN TANETE RIATTANG KABUPATEN BONE - Jauhar, Sitti; Jafar, Muhammad Idris; Auliana, Linda (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The purpose of this study was to determine 1) the application of the Inside Outside strategy in social studies learning in class III of SDN 3 Negeri 7 Manurunge. 2) Before and after the Inside Outside strategy on interest in learning social studies in class SDN 3 Negeri 7 Manurunge 3) the effect after the Inside Outside strategy on interest in learning social studies in class SDN 3 Negeri 7 Manurunge. This study was conducted in May-June 2024 with a quantitative approach. Data collection was carried out with pre-tests, post-tests and questionnaires of 16 students with descriptive statistics and inferential statistics using data analysis of normality tests using the Kolmogorov Smirnov Normality Test, homogeneity and hypothesis tests. The results of this study indicate that 1) the application of the IOC strategy in social studies learning 2). Before the implementation of the IOC strategy, the average student interest in social studies was 65.62 in the medium category, while after the implementation of the IOC, students' interest in learning social studies increased with an average score of 91 in the high category. 3) The influence of the IOC strategy on the interest in learning social studies is included in the moderate category. This is indicated by the hypothesis test analysis that the calculated t value> t (5.427) is obtained from a significant value of 0.000 <0.05, so it can be concluded that Ha is accepted or the IOC strategy variable so that it can be concluded that the IOC strategy has a significant influence on the interest in learning social studies of class III students of SD Negeri 3 Negeri 7 Manurunge, Tanete Riattang District, Bone Regency